Molecular mechanisms controlling age‐associated B cells in autoimmunity. Issue 1 (31st January 2022) - Phalke, Swati; Rivera‐Correa, Juan; Jenkins, Daniel; Flores Castro, Danny; Giannopoulou, Evgenia; Pernis, Alessandra B.
Abstract: Age‐associated B cells (ABCs) have emerged as critical components of immune responses. Their inappropriate expansion and differentiation have increasingly been linked to the pathogenesis of autoimmune disorders, aging‐associated diseases, and infections. ABCs exhibit a distinctive phenotype and, in addition to classical B cell markers, often express the transcription factor T‐bet and myeloid markers like CD11c; hence, these cells are also commonly known as CD11c + T‐bet + B cells. Formation of ABCs is promoted by distinctive combinations of innate and adaptive signals. In addition to producing antibodies, these cells display antigen‐presenting and proinflammatory capabilities. It is becoming increasingly appreciated that the ABC compartment exhibits a high degree of heterogeneity, plasticity, and sex‐specific regulation and that ABCs can differentiate into effector progeny via several routes particularly in autoimmune settings. In this review, we will discuss the initial insights that have been obtained on the molecular machinery that controls ABCs and we will highlight some of the unique aspects of this control system that may enable ABCs to fulfill their distinctive role in immune responses. Given the expanding array of autoimmune disorders and pathophysiological settings in which ABCs are being implicated, a deeper understanding of this machinery could have important and broad therapeutic implications for the successful, albeit daunting, task of targeting these cells.